Radio-dating analysis and reconstruction of past events in a semi-closed deep basin, north Cretan Basin - Maniati, Zoi; Tsabaris, Christos; Androulakaki, Effrosyni; Alexakis, Stylianos; Patiris, Dionisis; Manta, K.; Kokkoris, Michael (HNPS Advances in Nuclear Physics, 2026)
The present study investigates recent environmental variations and potential contamination within a semi-enclosed marine basin by examining sediment cores, which serve as both archives and ultimate sinks of particulate and dissolved matter. Sediment samples were retrieved using a box corer and analyzed through high-resolution gamma-ray spectrometry to quantify radionuclide activities and determine bulk density. The sedimentation rate was derived from the depth distribution of excess 210Pb, with 226Ra used as a supporting radionuclide for equilibrium assessment. A distinct tephra layer identified at 10.5 cm depth was radiometrically dated to approximately 1650 CE, indicating deposition from the Kolumbo volcanic eruption. Notably, the peak activity of natural radionuclides occurs at 9.5 cm, reflecting post-eruptive sedimentary processes. The lower values of the sedimentation rate observed in this deep basin, compared to the basins of the North and central Aegean Sea, is attributed to its remoteness from direct terrestrial inputs. Furthermore, the relationship between 226Ra and 212Pb delineates two distinct depositional regimes—one preceding and one following the tephra horizon—demonstrating differences in sediment dynamics and related processes.